2008
DOI: 10.1242/jcs.006064
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular matrix dynamics in development and regenerative medicine

Abstract: The extracellular matrix (ECM) regulates cell behavior by influencing cell proliferation, survival, shape, migration and differentiation. Far from being a static structure, the ECM is constantly undergoing remodeling – i.e. assembly and degradation – particularly during the normal processes of development, differentiation and wound repair. When misregulated, this can contribute to disease. ECM assembly is regulated by the 3D environment and the cellular tension that is transmitted through integrins. Degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
738
0
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 868 publications
(751 citation statements)
references
References 134 publications
(104 reference statements)
7
738
0
6
Order By: Relevance
“…Periostin is a member of a subset of secreted ECM-associated molecules termed "matri-cellular" proteins [48][49][50] that modulate interactions with structural components of the ECM, such as collagens, and a variety of cell surface receptors, such as integrins, to regulate cellular differentiation in development [51] and connective tissue disease [52]. Based on these data and numerous studies demonstrating that the ECM can potently regulate cellular differentiation [53][54][55][56][57], where possible we incorporated our periostin treatments into the collagen substrate, rather than simply amending the tissue culture media, to more closely replicate in vivo conditions. Periostin has been shown to promote collagen fibrillogenesis and alter the deposition of ECM proteins in other systems [58] and larger scale microarray studies have identified COL1A1 mRNA, encoding the collagen α1 component of heterotrimeric and homotrimeric type-1 collagen [59], as up-regulated in DD cord [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Periostin is a member of a subset of secreted ECM-associated molecules termed "matri-cellular" proteins [48][49][50] that modulate interactions with structural components of the ECM, such as collagens, and a variety of cell surface receptors, such as integrins, to regulate cellular differentiation in development [51] and connective tissue disease [52]. Based on these data and numerous studies demonstrating that the ECM can potently regulate cellular differentiation [53][54][55][56][57], where possible we incorporated our periostin treatments into the collagen substrate, rather than simply amending the tissue culture media, to more closely replicate in vivo conditions. Periostin has been shown to promote collagen fibrillogenesis and alter the deposition of ECM proteins in other systems [58] and larger scale microarray studies have identified COL1A1 mRNA, encoding the collagen α1 component of heterotrimeric and homotrimeric type-1 collagen [59], as up-regulated in DD cord [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in these interactions as a consequence of ECM remodeling give rise to specific cell‐signaling and intracellular cascades. These processes are central to physiology and pathological processes, such as tissue self‐repair and tumorigenesis 1b,1c. As mimics of such dynamic interactions, artificial matrices with the reversible display of bioactive ligands have attracted much attention.…”
mentioning
confidence: 99%
“…The ECM determines cell behavior by manipulating cell shape, proliferation, migration, differentiation, and death. 71 Scarless regenerative healing is an intrinsic property of the fetal skin. 72 Major differences in the ECM of the fetal and the adult skin account for the sharp contrast in healing phenotype between the fetus and adult skin.…”
Section: Mirna and Regenerative Medicinementioning
confidence: 99%